Bulbar involvement and cognitive features in amyotrophic lateral sclerosis: a retrospective study on 347 patients - Aiello, Edoardo Nicolò; Solca, Federica; Torre, Silvia; Patisso, Valerio; De Lorenzo, Alberto; Treddenti, Mauro; Colombo, Eleonora; Maranzano, Alessio; Morelli, Claudia; Doretti, Alberto; Verde, Federico; Silani, Vincenzo; et al. (Frontiers in Aging Neuroscience, 2023)
Background. This study aimed at clarifying the role of bulbar involvement (BI) as a risk factor for cognitive impairment (CI) in non-demented amyotrophic lateral sclerosis (ALS) patients. Methods. Data on N=347 patients were retrospectively collected. Cognition was assessed via the Edinburgh Cognitive and Behavioural ALS Screen (ECAS). On the basis of clinical records and ALS Functional Rating Scale-Revised (ALSFRS-R) scores, BI was characterized as follows: 1) BI at onset – from medical history ; 2) BI at testing (an ALSFRS-R-Bulbar score ≤11); 3) dysarthria (a score ≤3 on item 1 of the ALSFRS-R); 4) severity of BI (the total score on the ALSFRS-R-Bulbar); and 5) progression rate of BI (computed as 12-ALSFRS-R-Bulbar/disease duration in months). Logistic regressions were run to predict a below- vs. above-cutoff performance on each ECAS measure based on BI-related features while accounting for sex, disease duration, severity and progression rate of respiratory and spinal involvement and ECAS response modality. Results. No predictors yielded significance either on the ECAS-Total and -ALS-nonspecific or on ECAS-Language/-Fluency or -Visuospatial subscales. BI at testing predicted a higher probability of an abnormal performance on the ECAS-ALS-specific (p=.035) and ECAS-Executive Functioning (p=.018). Lower ALSFRS-R-Bulbar scores were associated with a defective performance on the ECAS-Memory (p=.025). No other BI-related features affected other ECAS performances. Discussion. In ALS, the occurrence of BI itself, while neither its specific features nor its presence at onset, might selectively represent a risk factor for executive impairment, whilst its severity might be associated with memory deficits.